Efficacy of Baricitinib in Patients with Various Degrees of Alopecia Areata Severity: Post-Hoc Analysis from BRAVE AA1 and BRAVE AA2 - Susan Taylor; Neil J. Korman; Tsen-Fang Tsai; Yutaka Shimomura; Meghan Feely; Yves Dutronc; Wen-Shuo Wu; Najwa Somani; Antonella Tosti (Adis, Springer Healthcare, 2023)
Abstract Background Baricitinib, an oral selective JAK1/JAK2 inhibitor, is approved for the treatment of adults with severe alopecia areata (AA). Objective To evaluate differences in response up to week 52 among subgroups based on the baseline severity of AA assessed with the Severity of Alopecia Tool (SALT) score. Methods Data were pooled from BRAVE-AA1 and BRAVE-AA2, two randomized, placebo-controlled, phase 3 trials, which enrolled adults with a SALT score ≥ 50. Patients were subdivided by the degree of AA severity at baseline. Results Among the 855 patients treated with baricitinib 2 mg and 4 mg, improvements in scalp hair growth continued through to week 52. A superior response was observed in patients with a SALT score of 50-94 versus a score of 95-100. Patients on baricitinib 4 mg had a faster and higher response rate compared to baricitinib 2 mg. Conclusion Across all degrees of severity for baricitinib 2 mg and 4 mg doses, the proportion of patients responding was yet to plateau up to week 52. Response to treatment was longer for patients with a baseline SALT score 95-100. Further studies are needed to analyze other parameters that may impact observed response rates.